Improved Charge Injection and Transport of Light-Emitting Diodes Based on Two-Dimensional Materials - Yuanming Zhou; Sijiong Mei; Dongwei Sun; Neng Liu; Fei Mei; Jinxia Xu; Xianan Cao (Applied Sciences, 2019)
Light-emitting diodes (LEDs) are considered to be the most promising energy-saving technology for future lighting and display. Two-dimensional (2D) materials, a class of materials comprised of monolayer or few layers of atoms (or unit cells), have attracted much attention in recent years, due to their unique physical and chemical properties. Here, we summarize the recent advances on the applications of 2D materials for improving the performance of LEDs, including organic light emitting diodes (OLEDs), quantum dot light emitting diodes (QLEDs) and perovskite light emitting diodes (PeLEDs), using organic films, quantum dots and perovskite films as emission layers (EMLs), respectively. Two dimensional materials, including graphene and its derivatives and transition metal dichalcogenides (TMDs), can be employed as interlayers and dopant in composite functional layers for high-efficiency LEDs, suggesting the extensive application in LEDs. The functions of 2D materials used in LEDs include the improved work function, effective electron blocking, suppressed exciton quenching and reduced surface roughness. The potential application of 2D materials in PeLEDs is also presented and analyzed.